2012
DOI: 10.1111/j.1525-139x.2012.01103.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Implantable Electronic Device Leads in CKD and ESRD Patients: Review and Recommendations for Practice

Abstract: Cardiovascular implantable electronic devices (CIEDs) are frequently utilized for management of cardiac dysrhythmias in patients with chronic kidney disease or end-stage renal disease receiving hemodialysis. The survival benefit from use of implantable cardioverter defibrillators in patients with CKD or ESRD is not as clear as in the general population, particularly when used for primary prevention of sudden cardiac death. Transvenous CIED leads are associated with central vein stenosis resulting in significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 96 publications
(103 reference statements)
1
43
0
3
Order By: Relevance
“…A retrospective study found that patients on chronic dialysis who received an S‐ICD had no device‐related infections over a mean follow‐up of 7 months 87. Moreover, a reduced risk of central venous stenosis and hematogenous and endocardial bacterial infections was noted in a recent case series 89. This result was later confirmed in other studies 90.…”
Section: Chf In Patients With Esrdmentioning
confidence: 75%
“…A retrospective study found that patients on chronic dialysis who received an S‐ICD had no device‐related infections over a mean follow‐up of 7 months 87. Moreover, a reduced risk of central venous stenosis and hematogenous and endocardial bacterial infections was noted in a recent case series 89. This result was later confirmed in other studies 90.…”
Section: Chf In Patients With Esrdmentioning
confidence: 75%
“…Most patients with end-stage renal disease (ESRD) under hemodialysis appear multiple complications, especially cardiovascular disease [1]. High fluid intake from daily diet leads to high inter dialytic weight gain (IDWG) in patients during dialysis session.…”
Section: Introductionmentioning
confidence: 99%
“…Subcutaneous ICD (S‐ICD) implantation in dialysis patients is not associated with an excess risk of implant‐related complications . Several other studies reported a reduced incidence of central vein stenosis and bloodstream mediated infection with S‐ICD . Therefore, considering the elevated risk of SCD in ESRD patients, S‐ICD may be recommended for primary prevention of SCD.…”
Section: End‐stage Renal Disease and Sudden Cardiac Deathmentioning
confidence: 99%